Gastroenteropancreatic neuroendocrine tumors: clinicopathological evaluation at Shifa International Hospital, Islamabad. A single centre experience - Nadira Mamoon; Hania Naveed; Mariam Abid; Humaira Nasir; Imran Nazir Ahmad; Zujajah Hameed; Asna Haroon Khan (Journal of the Pakistan Medical Association, 2020)
Objective: Clinicopathological features of gastroenteropancreatic neuroendocrine tumors (GEP-NETs) have rarely been studied in the Pakistani population. We investigated the clinical characteristics of these tumors according to the updated World Health Organization (WHO) 2010 classification. Methods: The data of Shifa International Hospital, Islamabad was retrospectively analysed for pathologically confirmed GEP-NETs from January 2013 to March 2018. Results: One hundred and eighteen patients (mean age, 52.2 years; male, 55.1%) were identified. 83.1% of the patients were symptomatic including5.1% functional tumors. Pancreas (28%) was the most frequent primary site noted. The most common histologic type was well differentiated neuroendocrine tumor (WDNET) in 81.4% followed by neuroendocrine carcinoma (NEC) in 16.1%. 45.8% cases of WDNET were grade 1, 27.1% were grade 2, and 8.5% were grade 3.15.3% had distant metastasis at the time of diagnosis with liver (77.7%) as the most common metastatic site. Synaptophysin positivity was seen in 96.8% of grade 1 & grade 2 WDNET, 100% of grade 3 WDNET and 92.3% of NEC and chromogranin was positive in 94.2% of grade 1 &grade 2 WDNET, 83.3% of grade 3 WDNET and 45.4% of NEC. Conclusion: GEP-NETs showed a wide clinicopathological spectrum. Pancreas is the most site of involvement by the GEP-NET however grade 3 WDNET had a predilection for the colon. Small cell carcinomas were commonly observed in esophagus. Keywords: Gastroenteropancreatic neuroendocrine tumor, well differentiated neuroendocrine tumor, neuroendocrine carcinoma. Continuous...